Electrospinning of SnO2-TiO2 nanofiber/nanorod composites for uses as electron transport layers in flexible perovskite solar cells - Methawee Nukunudompanich; Kamonchanok Roongraung; Kanyanee Sanglee; Wassana Lekkla; Surawut Chuangchote (AIP conference proceedings, 2024)
In perovskite solar cells (PSCs), the most commonly used electron transport layers (ETLs) are titanium dioxide (TiO 2 ) and tin oxide (SnO 2 ).The problem with SnO 2 is that its conduction band does not match that of perovskites, while TiO 2 's photocatalytic nature can destroy perovskite materials.Additionally, these ETLs are typically applied in the form of nanoparticles.Electrospinning was used to produce composite nanofibers or nanorods of SnO 2 -TiO 2 to improve the photovoltaic performance of flexible PSCs, which are required for flexible electronic devices.SnO 2 -TiO 2 nanofibers or NRs as ETLs assist perovskites in harvesting light, separating excitons, extracting and collecting electrons, blocking holes, and preventing perovskites from decomposing and forming defects.PSCs containing SnO 2 -TiO 2 nanoparticles have been produced.From the J-V characteristics of flexible-PSCs, the use of SnO 2 -TiO 2 nanofibers improved the power conversion efficiency of the solar cells.A higher current density was obtained.This occurs because the 1D structure allows for more freely moving electrons.Comparing SnO 2 nanoparticles and TiO 2 nanofibers, an SnO 2 -TiO 2 layer provides superior charge mobility and helps improve strength of the bonding at the perovskite/ITO interface.It is superior to SnO 2 NPs and TiO 2 nanofibers in reducing surface recombination.
Keywords: Perovskite Materials and Applications; Conducting polymers and applications; Advanced Sensor and Energy Harvesting Materials